IoT Based PDAM Water Meter Monitoring System With Real Time Data: Sistem Pemantauan Meteran Air PDAM Berbasis IoT dengan Data Real-Time - Radika Saifuddin; Shazana Dhiya Ayuni (Indonesian Journal of Innovation Studies, 2026)
General Background: Water is a vital resource, and increasing demand requires accurate monitoring systems. Specific Background: Conventional PDAM water meters face limitations in accuracy, real-time monitoring, and data recording. Knowledge Gap: Existing systems lack integrated real-time monitoring with unlimited database storage for long-term usage tracking. Aims: This study aims to develop an Internet of Things based water meter monitoring system using ESP32 and YF-S201 sensor to measure water usage and cost. Results: The system displays real-time data via LCD and Blynk application while storing data in Google Spreadsheet, with an average flow error of 1.023% and cost error of 1.285%. A 30-day test recorded total water usage of 30,408.55 liters with a cost of Rp150,729.06. Novelty: The integration of real-time monitoring with automatic cloud-based data storage without capacity limitation distinguishes this system from previous studies. Implications: This system supports accurate recording, improves transparency, and offers a scalable digital solution for modern water distribution monitoring. Keywords: Internet of Things, Water Monitoring, ESP32, Water Flow Sensor, PDAM System Key Findings Highlights Real-time monitoring system records consumption and cost with low measurement deviation Cloud-based storage enables continuous and unlimited data logging Monthly testing demonstrates stable system performance in practical use